![image](https://tex.z-dn.net/?f=+%5Csqrt%7B4-7x%7D%3D2x%2B1%5C%5C2x%2B1+%5Cgeq+0%5C%5C2x+%5Cgeq+-1%5C%5Cx+%5Cgeq+-0%2C5%5C%5C%5C%5C++%28%5Csqrt%7B4-7x%7D%29%5E2%3D%282x%2B1%29%5E2%5C%5C4-7x%3D4x%5E2%2B4x%2B1%5C%5C4x%5E2%2B4x%2B7x%2B1-4%3D0%5C%5C4x%5E2%2B11x-3%3D0%5C%5CD%3D11%5E2-4%2A4%2A%28-3%29%3D121%2B48%3D169%3D13%5E2%5C%5C%5C%5Cx_1%3D+%5Cfrac%7B-11%2B13%7D%7B2%2A4%7D%3D+%5Cfrac%7B-2%7D%7B8%7D%3D-0%2C25%3E-0%2C5%5C%5C%5C%5Cx_2%3D+%5Cfrac%7B-11-13%7D%7B2%2A4%7D%3D++%5Cfrac%7B-24%7D%7B8%7D%3D-3%3C-0%2C5%5C%5C%5C%5Cx%3D-0%2C25++)
-0,5\\\\x_2= \frac{-11-13}{2*4}= \frac{-24}{8}=-3<-0,5\\\\x=-0,25 " alt=" \sqrt{4-7x}=2x+1\\2x+1 \geq 0\\2x \geq -1\\x \geq -0,5\\\\ (\sqrt{4-7x})^2=(2x+1)^2\\4-7x=4x^2+4x+1\\4x^2+4x+7x+1-4=0\\4x^2+11x-3=0\\D=11^2-4*4*(-3)=121+48=169=13^2\\\\x_1= \frac{-11+13}{2*4}= \frac{-2}{8}=-0,25>-0,5\\\\x_2= \frac{-11-13}{2*4}= \frac{-24}{8}=-3<-0,5\\\\x=-0,25 " align="absmiddle" class="latex-formula">